Internet sport bloggers: Who are these people and where do they come from? - Edward M. Kian; Joe W. Burden Jr.; Stephanie D. Shaw (Journal of Applied Sports Management, 2011)
Little is known of Internet sport bloggers, who increasingly are becoming important cogs in sport journalism. In this phenomenology, semi-structured interviews were conducted with highly prominent sport bloggers. All were recorded, transcribed, and coded. A total of five dominant themes emerged from the data that focused on the shared experiences and learned attitudes toward Internet sport journalism. Overall, these themes showed sport bloggers were highly educated and very happy with their jobs, had a wide array of past work experiences that often had little to no relation with blogging or sport journalism, consider their jobs too varied to fall under one title, primarily work from home, and rarely attend sporting events they write about.
Keywords: sport bloggers; sport journalism; blogging; sport careers